Argentina y sus vínculos con las monarquías del golfo durante la gestión de Alberto Fernández. Del impacto de la pandemia a la apuesta por exportar conocimiento y obtener financiamiento externo (2019-2023) - Fabani, Ornela (2025)
Argentina established diplomatic relations with the Gulf monarchies —Saudi Arabia, Bahrain, the United Arab Emirates, Kuwait, Qatar, and Oman— decades ago. However, these relations only gained significant depth starting with the second government of the Frente Para la Victoria (FPV). The guiding question of this research is: ¿how have Argentina’s ties with the Gulf monarchies evolved during Alberto Fernández’s administration (2019-2023)? In seeking to answer this question, the study aims to: describe the course of relations with these six countries during the period under review, identify the key actors driving these ties, examine their objectives, and finally, analyze the internal and external factors that have shaped the trajectory of these relationships. Methodologically, the research is based on a qualitative approach, relying on data collection and analysis from both primary and secondary sources. Among the primary sources, unstructured interviews stand out.